IMPLIKASI MARKET VALUE, VARIAN RETURN, LABA PER SAHAM DAN DEVIDEN TERHADAP BID-ASK SPREAD SAHAM SYARIAH - Fitriyah, Fitriyah (Fakultas Ekonomi, UIN Maliki Malang, 2012)
This research was aimed to determine whether the variables variance return, market value, dividend and earning per share influence the bid-ask spread partially and simultaneously of shares of sharia in Indonesia Stock Exchange. The population in this research are the companies listed in the Jakarta Islamic Index over the period 2007 to 2010. Sampling using a purposive sampling technique and number of sample are 10 companies. The result shows, the variance return, market value, dividend and earning per share simultaneously influence the bid-ask spread. While partially, there ar three variables that significantly influence the bid-ask spread that is variance return with significant positif, dividend, and erningper share with a significant negative relationship. Variable market value does not affect the bid ask spread. Increase in variance return would cause the dealer / broker to cover the high spread. The existence of dividend payments and earnings per share would have an impact on high stock trading so dealers will not take long to save the stock This results in reduced inventory holding cost and ultimately lower the bid ask spread.